The Implementation of Project-Based Learning Assisted by GeoGebra-Based Ludomatika to Improve Students' Mathematics Learning Outcomes in Social Arithmetic - Endang Anjarwarti; Sarson W. Dj. Pomalato; Kartin Usman (Scimadly Publishing, 2026)
This study aims to improve students' mathematics learning outcomes in social arithmetic through the implementation of the Project-Based Learning (PjBL) model assisted by GeoGebra-based Ludomatika media in class VII-1 of SMP Negeri 11 Dumoga. This study employed a classroom action research (CAR) design conducted in the 2024/2025 academic year, involving 30 students of class VII-1 as research subjects. The study was conducted in two cycles, each consisting of planning, action implementation, observation, and reflection stages. Data were collected through tests and observations using essay tests and observation sheets for teacher and student activities. The results showed an improvement in students' learning outcomes following the implementation of learning assisted by GeoGebra-based Ludomatika. In addition, teacher activity increased from 77.77% in Cycle I to 83.33% in Cycle II, while student activity increased from 69.70% to 80.60%. These improvements indicate that the implementation of Project-Based Learning assisted by GeoGebra-based Ludomatika can support the improvement of students' mathematics learning outcomes in social arithmetic. Therefore, the use of this media can serve as an alternative to support the mathematics learning process in the classroom.